GERAKAN SASTRA KEAGAMAAN DI INDONESIA SESUDAH REFORMASI 1998 - Ronidin Ronidin (Puitika, 2016)
This article aims to describe the movement of religious literature in Indonesia after the 1998 reform. The movement embodied in authorship organization called Forum Lingkar Pena (FLP). FLP grow and develop in that time as the implications of modernist Islamic movement that carried the young people educated in various universities in Indonesia. As one of the literary community, FLP trying to popularize transcendental literary movement that is not profane and worldly. FLP be the community of Islamic literature that trying to enlighten the public with literature. During its development, the literary movement of FLP community into one of the vehicle for thousands of young Indonesian to make literature as a medium a mental reform based on Islamic values. Movement conducted by FLP is a creative alternative to the development of Islamic literature in Indonesia.